IgG4-related disease in the sinonasal cavity accompanied by intranasal structure loss. Issue 1 (February 2016) - Inoue, Akiko; Wada, Kota; Matsuura, Kentaro; Osafune, Hiroshi; Ida, Yutaro; Kosakai, Arifumi; Edamatsu, Hideo
Abstract: IgG4-related disease was recently proposed under the classification of systemic chronic inflammatory disease. In the field of otolaryngology, organ-specific diagnostic criteria have been established for the occurrence of this condition in the salivary glands, but not in the sinonasal cavity. Here we report a case involving a 70-year-old man with IgG4-related disease in the sinonasal cavity. The patient, with the chief complaint of nasal bleeding, first visited a physician. However, the patient experienced recurrent bleeding with intranasal structure loss and was subsequently referred to our hospital. His IgG4 level was elevated, and histopathological examination of a tissue sample obtained from the edematous sphenoid sinus showed increased IgG4-positive plasma cells and storiform fibrosclerosis. A definitive diagnosis of IgG4-related rhinosinusitis was made on the basis of comprehensive criteria for IgG4-related disease. The disease showed a progressively destructive course that was clearly different from that of chronic sinusitis and represented a very rare case of IgG4-related rhinosinusitis. IgG4-related disease originating in the sinonasal cavity is rare, and, to the best of our knowledge, this is the first primary case of IgG4-related disease that originated in one side of the sinonasal cavity and showed progressive destruction.